Symphyotrichum subulatum (Michx.) G.L. Nesom (Asteraceae): Addition to the Flora of Himachal Pradesh, India - Dogra, Kuldip S.; Sharma, Bhagwati Prashad; Chandel, Sangeeta; Ambrish, Kumar; Singh, Ritesh K.; Meena, Brajesh (Indian Forester, 2025)
No Abstract.